Databases, Information Systems, and Peer-to-Peer Computing International Workshops, DBISP2P 2005/2006, Trondheim, Norway, August 28-29, 2006, Revised Selected Papers - Moro, Gianluca; Bergamaschi, Sonia; Joseph, Sam.; Morin, Jean-Henry.; Ouksel, Aris M.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
The aim of the International Workshop on Databases, Information Systems and P2P Computing was to explore the promise of P2P to o?er exciting new p- sibilities in distributed information processing and database technologies. The realization of this promise lies fundamentally in the availability of enhanced services such as structured ways for classifying and registering shared infor- tion, veri?cation and certi?cation of information, content distributed schemes and quality of content, security features, information discovery and accessib- ity, interoperation and composition of active information services, and ?nally market-based mechanisms to allow cooperative and noncooperative information exchanges. The P2P paradigm lends itself to constructing large-scale, complex, adaptive, autonomous and heterogeneous database and information systems, endowed with clearly speci?ed and di?erential capabilities to negotiate, bargain, coordinate and self-organize the information exchanges in large-scale networks. This vision will have a radical impact on the structure of complex organizations (business, sci- ti?c or otherwise) and on the emergence and the formation of social communities, and on how the information is organized and processed. The P2P information paradigm naturally encompasses static and wireless connectivity and static and mobile architectures. Wireless connectivity combined with the increasingly small and powerful mobile devices and sensors poses new challenges as well as opp- tunities to the database community. Information becomes ubiquitous, highly distributed and accessible anywhere and at any time over highly dynamic, - stable networks with very severe constraints on the information management and processing capabilities.
Third Edition -- Galois Connections, T-CUBES, and P2P Data Mining -- Querying a Super-Peer in a Schema-Based Super-Peer Network -- Query Answering and Overlay Communities -- Database Selection and Result Merging in P2P Web Search -- Multiple Dynamic Overlay Communities and Inter-space Routing -- Benefit and Cost of Query Answering in PDMS -- Indexing, Caching and Replication Techniques -- Cooperative Prefetching Strategies for Mobile Peers in a Broadcast Environment -- Symmetric Replication for Structured Peer-to-Peer Systems -- A Gradient Topology for Master-Slave Replication in Peer-to-Peer Environments -- Complex Query Processing and Routing -- A Content–Addressable Network for Similarity Search in Metric Spaces -- Range Query Optimization Leveraging Peer Heterogeneity in DHT Data Networks -- Guaranteeing Correctness of Lock-Free Range Queries over P2P Data -- Publish/Subscribe with RDF Data over Large Structured Overlay Networks -- Semantic Overlay Networks -- A Semantic Information Retrieval Advertisement and Policy Based System for a P2P Network -- Cumulative Algebraic Signatures for Fast String Search, Protection Against Incidental Viewing and Corruption of Data in an SDDS -- PARIS: A Peer-to-Peer Architecture for Large-Scale Semantic Data Integration -- Processing Rank-Aware Queries in P2P Systems -- Semantic Caching in Schema-Based P2P-Networks -- Aggregation of a Term Vocabulary for P2P-IR: A DHT Stress Test -- Services, Agents and Communities of Interest -- Peer Group-Based Dependency Management in Service-Oriented Peer-to-Peer Architectures -- LEAP-DB: A Mobile-Agent-Based Distributed DBMS Not Only for PDAs -- Models and Languages for Overlay Networks -- A Peer-to-Peer Membership Notification Service -- Querying Communities of Interest in Peer Database Networks -- Fourth Edition -- Middleware for Reliable Real-Time Sensor Data Management -- Data Placement and Searching -- Oscar: Small-World Overlay for Realistic Key Distributions -- Keyword Searching in Structured Overlays Via Content Distance Addressing -- Semantic Search -- XML Query Routing in Structured P2P Systems -- Reusing Classical Query Rewriting in P2P Databases -- Efficient Searching and Retrieval of Documents in PROSA -- P2P Query Reformulation over Both-As-View Data Transformation Rules -- RDFCube: A P2P-Based Three-Dimensional Index for Structural Joins on Distributed Triple Stores -- Query Processing and Workload Balancing -- Optimal Caching for First-Order Query Load-Balancing in Decentralized Index Structures -- On Triple Dissemination, Forward-Chaining, and Load Balancing in DHT Based RDF Stores -- Priority Based Load Balancing in a Self-interested P2P Network -- A Self-organized P2P Network for an Efficient and Secure Content Location and Download -- Query Coordination for Distributed Data Sharing in P2P Networks -- Continuous Queries and P2P Computing -- A Comparative Study of Pub/Sub Methods in Structured P2P Networks -- Answering Constrained k-NN Queries in Unstructured P2P Systems -- Scalable IPv4/IPv6 Transition: A Peer-to-Peer Based Approach.
Keywords: Computer communication systems; Database management; Information storage and retrieval; Application software; Software engineering; Artificial intelligence; Computer Communication Networks; Database Management; Information Storage and Retrieval; Information Systems Applications (incl. Internet).; Software Engineering; Artificial Intelligence